PERAN INDEKS PEMBANGUNAN MANUSIA DAN JUMLAH PENDUDUK DALAM MENDORONG PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA UTARA - Rexsy Mardohot Sitanggang; Karolin Gabrela Sitanggang; Rebecca Putri Sihaloho; Nabila Umaira; Nadia Natalia Sinurat; Lokot Muda Harahap (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study examines the relationship between the Human Development Index (HDI) and population size with economic growth in North Sumatra Province during 2010-2025 using multiple linear regression based on secondary data. The results indicate that both variables are jointly associated within the model, although they show different directions when observed individually. Population size tends to move in line with economic growth, while HDI shows an opposite tendency. These findings suggest that improvements in human capital have not yet been fully reflected in productive economic activities in the region.